Crack-free in situ heat-treated high-alloy tool steel processed via laser powder bed fusion: microstructure and mechanical properties - Simon Bergmueller; Lukas Kaserer; Lorenz Fuchs; Jakob Braun; Nikolaus Weinberger; Ilse Letofsky-Papst; Gerhard Leichtfried (Heliyon, 2022)
In this study, high-alloy tool steel S390 was processed crack-free and dense for the first time using laser powder bed fusion (LPBF). The resulting mechanical properties and microstructure of the LPBF steel parts were investigated. High-alloy tool steels, such as high-performance high-speed Boehler S390 steel (containing 1.64 wt% C and W, Mo, V, Co, and Cr in the ratio 10:2:5:8:5 wt%), are prone to cracking when processed using LPBF because these steels have high carbon and carbide-forming alloying elements content. Cracks are induced by thermal stresses and solid-phase transformation, combined with weak grain boundaries caused by segregated primary carbides. Substrate plate heating reduces thermal stresses and enables in situ heat treatment, thus modulating solid-phase transformation and carbide precipitation and preventing cracking during cooling. The resulting microstructure, precipitations, and mechanical properties of the as-built LPBF specimens, which were in situ heat-treated at 800 °C, and the conventionally post-heat-treated specimens were assessed using optical microscopy, scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, electron backscatter diffraction, X-ray diffraction, hardness testing, bending testing, and density measurement. In situ heat treatment impacts microstructure, precipitation behavior, and solid-phase transformation, causing a change in the microstructure of the material along the build direction due to different thermal histories. The as-built specimens exhibit a hardness gradient along the build direction of 500 HV1 to 800 HV1 in the top layer. The average bending strength is 2500 MPa, measured from the tensile stresses on the harder side and the compressive stresses on the softer side. Conventional post-heat treatment yields a mean hardness of 610 HV1 and a mean bending strength of 2800 MPa.